Finite element analysis of the stress distributions in peri-implant bone in modified and standard-threaded dental implants - Dundar, Serkan; Topkaya, Tolga; Solmaz, Murat Yavuz; Yaman, Ferhan; Atalay, Yusuf; Saybak, Arif; Cakmak, Omer (Taylor & Francis Ltd, 2016)
The aim of this study was to examine the stress distributions with three different loads in two different geometric and threaded types of dental implants by finite element analysis. For this purpose, two different implant models, Nobel Replace and Nobel Active (Nobel Biocare, Zurich, Switzerland), which are currently used in clinical cases, were constructed by using ANSYS Workbench 12.1. The stress distributions on components of the implant system under three different static loadings were analysed for the two models. The maximum stress values that occurred in all components were observed in F-III (300 N). The maximum stress values occurred in F-III (300 N) when the Nobel Replace implant is used, whereas the lowest ones, in the case of F-I (150 N) loading in the Nobel Active implant. In all models, the maximum tensions were observed to be in the neck region of the implants. Increasing the connection between the implant and the bone surface may allow more uniform distribution of the forces of the dental implant and may protect the bone around the implant. Thus, the implant could remain in the mouth for longer periods. Variable-thread tapered implants can increase the implant and bone contact.
Keywords: Finite element analysis; dental implant design; stress distribution; oblique loading; thread design